High-wear-resistance stainless steel band
By spraying a wear-resistant coating composed of modified graphene, modified nanocellulose and polyvinyl alcohol on the surface of the stainless steel belt, a stable three-dimensional network structure is formed, which solves the wear problem of stainless steel belt and significantly improves wear resistance and mechanical strength. Extend service life.
Patent Information
- Application Number
- CN202411528783.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-10
AI Technical Summary
The wear problem of stainless steel belts affects the service life of the product, and the prior art is difficult to effectively improve its wear resistance.
Wear-resistant coatings are used to combine modified graphene, modified nanocellulose and polyvinyl alcohol to form graphene composite components, and form a stable three-dimensional network structure through hydrogen bond interaction to improve the mechanical strength and wear resistance of steel belts. and adhere it to the surface of the stainless steel strip by spraying technology.
It significantly improves the wear resistance and mechanical strength of stainless steel strips, extends the service life, and enhances the stability and dispersion of the paint.
Smart Images

Figure BDA0005109959120000081 
Figure BDA0005109959120000091
Abstract
Description
Technical Field
[0001] The present application relates to the field of stainless steel, and in particular to a high wear-resistant stainless steel belt. Background Art
[0002] Stainless steel strip is an extension of stainless steel plate, mainly used to meet the needs of metal or mechanical products in different industrial sectors. Stainless steel strip is a narrow and long steel plate, usually made of high carbon steel or alloy steel through a series of processing and treatment. It is a metal strip with stainless steel characteristics, a metal material with good mechanical properties and processing properties, and is widely used in various industrial fields.
[0003] With the development of industrial production, the performance requirements for stainless steel belts are further improved. The wear problem of stainless steel belts themselves will also affect the service life of the product, so it needs to be improved. Summary of the invention
[0004] In order to improve the wear resistance of the stainless steel belt, the present application provides a high wear-resistant stainless steel belt.
[0005] The present application provides a highly wear-resistant stainless steel belt adopts the following technical solution: A highly wear-resistant stainless steel strip comprises a steel strip body and a wear-resistant coating, wherein the wear-resistant coating is formed by attaching the wear-resistant coating to the surface of the steel strip body, and the wear-resistant coating comprises the following components in parts by weight: 105-115 parts of polyurethane, 52-64 parts of epoxy resin, 20-26 parts of graphene composite component, 3-5 parts of dispersant, 7-9 parts of leveling agent, 2-4 parts of defoaming agent; The graphene composite component comprises modified graphene, modified nanocellulose and polyvinyl alcohol.
[0006] By adopting the above technical scheme, after the wear-resistant coating is attached to the surface of the steel strip body, a wear-resistant coating is formed on the surface of the steel strip body. The graphene composite component in the wear-resistant coating has good wear resistance and protection performance, and can effectively improve the wear resistance of the stainless steel strip; the graphene composite component is modified by graphene, modified nanocellulose and polyvinyl alcohol. Graphene is a single-layer two-dimensional honeycomb lattice structure formed by tightly stacking carbon atoms, and has good mechanical properties. The interlayer effect of the modified graphene is significantly improved, which further improves the overall mechanical strength and wear resistance of the system; nanocellulose is a biopolymer with good biocompatibility and can well connect the systems. The modified nanocellulose has a smaller size, which can make the graphene composite component more stable. After the modified nanocellulose is composited with the modified graphene, they are connected by hydrogen bond interaction to obtain a stable three-dimensional network structure. The addition of polyvinyl alcohol further improves the overall dispersion and interaction of the system, so that the prepared wear-resistant coating has better wear resistance and mechanical strength, so as to improve the mechanical properties and wear resistance of the steel strip body.
[0007] Preferably, the modified graphene includes amination graphene and styrene.
[0008] By adopting the above technical scheme, modified graphene is obtained by loading styrene on the amino surface graphene. The modified graphene molecules have a rough surface and a uniform particle size, and can be more stable in the system, so that the modified graphene has good dispersibility and the anti-corrosion performance of the prepared modified graphene is further improved.
[0009] Preferably, the amino graphene is prepared by the following method: Graphene and water are mixed by ultrasound to obtain a graphene dispersion, polyvinyl pyrrolidone is added to the graphene dispersion, polyether amine is added after magnetic stirring, stirred and heated to reflux for reaction, filtered after the reaction, freeze-dried to obtain amino graphene.
[0010] By adopting the above technical scheme, the organic molecule polyetheramine is in situ grafted on the surface of graphene to obtain aminated graphene. The aminated graphene has better dispersion and compatibility properties. When the polyetheramine is grafted on the surface of graphene, part of the graphene is reduced and an amide reaction occurs, thereby repairing the disordered structure within the graphene surface, facilitating the subsequent loading of styrene, and effectively improving the stability of the graphene.
[0011] Preferably, the modified graphene is prepared by the following method: The aminated graphene is mixed with water, and after ultrasonic treatment, ammonia water is added, styrene and potassium persulfate aqueous solution are added while stirring, the stirring condition is maintained, the temperature is increased for reaction, hydrazine hydrate is added, the reaction is continued, and freeze-drying is performed after the reaction to obtain modified graphene.
[0012] By adopting the above technical solution, after styrene is loaded on the surface of amino-treated graphene, it can further overcome the van der Waals force between graphene sheets, further prevent the stacking of graphene sheets, make the graphene surface rich in oxygen-containing groups, and adjust the dispersion performance of graphene in the system, so that the prepared modified graphene is more stable.
[0013] Preferably, the mass ratio of the amino graphene to styrene is 1:(2.5-2.9).
[0014] By adopting the above technical solution, preferably the mass ratio between the amino graphene and styrene is within the above range, the dispersibility and wear resistance of the prepared modified graphene can be further improved, making the modified graphene more stable.
[0015] Preferably, the graphene composite component is prepared by the following method: The polyvinyl alcohol and water are mixed and heated, and modified graphene, modified nanocellulose and sodium chloride are added, and then n-hexadecane is added, sheared and emulsified, and then transferred to an ice water bath for ultrasonic treatment to obtain a graphene composite component.
[0016] By adopting the above technical scheme, after the modified nanocellulose, modified graphene and polyvinyl alcohol are compounded, hydrogen bonding occurs between the modified nanocellulose and the modified graphene, so that the modified graphene and the modified nanocellulose are spatially assembled to form a stable three-dimensional network structure, thereby further improving the overall stability of the prepared graphene composite component. At the same time, in the presence of polyvinyl alcohol, the dispersion performance of each component of the system is promoted. At the same time, polyvinyl alcohol and the modified graphene also interact with each other, so that the overall thermal stability and mechanical strength of the prepared graphene composite component are further improved, so that the prepared wear-resistant coating has good wear resistance, good stability and mechanical strength, and further improves the mechanical strength and stability of the steel belt body.
[0017] Preferably, the modified nanocellulose is prepared by the following method: The nanocellulose is added to sodium hydroxide for treatment, washed and dried, added to dimethyl sulfoxide solution for treatment, and washed to obtain prefabricated nanocellulose; hydrogen chloride, sulfuric acid and water are mixed to obtain a mixed acid solution, the prefabricated nanocellulose is mixed with the mixed acid solution, acid hydrolyzed, a large amount of water is added after hydrolysis, and centrifuged to obtain modified nanocellulose.
[0018] By adopting the above technical solution, the modified nanocellulose is spherical and has a uniform particle size, so that it can be better combined with the modified graphene, so that the prepared graphene composite component has good stability and mechanical strength.
[0019] Preferably, the mass ratio of the modified graphene, modified cellulose and polyvinyl alcohol is (3.3-3.5):1:2.5.
[0020] By adopting the above technical solution, the mass ratio between the modified graphene, modified cellulose and polyvinyl alcohol is preferably within the above range, which can further improve the overall stability of the prepared graphene composite component.
[0021] Preferably, the wear-resistant coating is prepared by the following method: The waterborne polyurethane, epoxy resin, graphene composite component, dispersant, leveling agent and defoamer are mixed and stirred to obtain the wear-resistant coating.
[0022] Preferably, the stainless steel strip includes the following preparation method: grinding the surface of the steel strip body, then cleaning the steel strip body with ethanol, drying, vertically reciprocatingly spraying a wear-resistant coating on the surface of the steel strip body and curing it, so that a wear-resistant coating is formed on the surface of the steel strip body to obtain a highly wear-resistant stainless steel strip.
[0023] In summary, the present application includes at least one of the following beneficial technical effects: 1. After the wear-resistant coating is attached to the surface of the steel strip body, a wear-resistant coating is formed on the surface of the steel strip body. The graphene composite component in the wear-resistant coating has good wear resistance and protection performance, and can effectively improve the wear resistance of the steel strip body. The graphene composite component is prepared by modified graphene, modified nanocellulose and polyvinyl alcohol. The modified graphene and the modified nanocellulose are combined by hydrogen bonds to obtain a stable three-dimensional network structure. The polyvinyl alcohol can promote the dispersion of the modified graphene and the modified nanocellulose, so that the prepared graphene composite component is more uniform and stable in the coating system, and the mechanical properties, wear resistance and stability of the wear-resistant coating are improved; 2. First, the graphene is amino-modified so that part of the graphene is reduced and undergoes an amide reaction, repairing the disordered structure within the graphene surface. Then, styrene is terminated on the surface of the amino-modified graphene, further overcoming the van der Waals force between the graphene sheets and preventing the stacking of the graphene sheets. This allows the graphene surface to have abundant oxygen-containing groups to adjust the dispersion of the graphene in the system, further improving the overall stability of the system. 3. After the nanocellulose is modified, it becomes spherical with uniform particle size, and can be more stably combined with the modified graphene, so that the prepared graphene composite component has a stable network structure, thereby improving the overall stability and mechanical strength of the system. DETAILED DESCRIPTION
[0024] The present application is further described in detail below with reference to the embodiments: Raw material description: All raw materials in the embodiment can be obtained commercially; among them, the dispersant is BYK dispersant 163, the leveling agent is polydimethylsiloxane (CAS No.: 31692-79-2), the defoaming agent is BYK-A530 defoaming agent, and the steel strip body used is 304 Austrian stainless steel, and the thickness of the steel strip body is 3.0 mm.
[0025] Example 1 Preparation of modified nanocellulose: 15 g of nanocellulose (CAS No.: 9004-34-6) was added to 125 g of sodium hydroxide, treated at 80° C. for 3 h, then washed with deionized water until neutral, dried at 60° C., added to 125 g of dimethyl sulfoxide solution after drying, treated at 80° C. for 3 h, and washed with deionized water to obtain prefabricated nanocellulose; 37% by mass of hydrogen chloride, 98% by mass of sulfuric acid and deionized water were mixed in a mass ratio of 1:3:6 to obtain a mixed acid solution, the prefabricated nanocellulose was mixed with the mixed acid solution, and then acid hydrolyzed at 65° C. for 8 h, a large amount of deionized water was added after hydrolysis, and a centrifuge was used to centrifuge at a speed of 10000 r / min to obtain modified nanocellulose.
[0026] Preparation of amino graphene: 10 g of graphene was mixed with 1000 mL of deionized water and ultrasonically treated for 15 min to obtain a graphene dispersion. 20 g of polyvinyl pyrrolidone (CAS No.: 9003-39-8) was added to the graphene dispersion and magnetically stirred for 30 min. The mixture was then heated to 90° C., 4.5 g of polyetheramine (CAS No.: 9046-10-0) was added, and the mixture was stirred at 400 r / min and heated to reflux for 10 h. After the reaction, the mixture was filtered until the pH value of the system was 7, and finally freeze-dried at -20° C. to obtain amino graphene.
[0027] Preparation of modified graphene: 5.71 g of aminated graphene was mixed with 500 g of deionized water, and after ultrasonic treatment for 15 min, ammonia water was added to adjust the pH value of the system to 9. In an atmosphere of nitrogen protection, 14.29 g of styrene (CAS No.: 100-42-5) and 20 mL of 15 mg / mL potassium persulfate (CAS No.: 7727-21-1) aqueous solution were added while stirring at 500 r / min. The stirring condition was maintained and the temperature was raised to 90 ° C for reaction for 6 h. 262.5 g of hydrazine hydrate was added and the reaction was continued under stirring conditions and a temperature of 90 ° C for 1 h. After the reaction, the modified graphene was obtained by freeze-drying at -20 ° C.
[0028] Preparation of graphene composite components: After mixing 11.03 g of polyvinyl alcohol (CAS No.: 9002-89-5) with deionized water, the temperature was raised to 95°C, 14.56 g of modified graphene, 4.41 g of modified nanocellulose and 30 g of sodium chloride were added, and then 120 g of n-hexadecane was added. The mixture was sheared and emulsified at a speed of 6000 r / min for 2 min, and then transferred to an ice water bath and ultrasonically treated at a power of 30% for 3 min to obtain a graphene composite component.
[0029] Preparation of wear-resistant coating: 105 g of waterborne polyurethane, 52 g of epoxy resin, 20 g of graphene composite component, 3 g of dispersant, 7 g of leveling agent and 2 g of defoaming agent were mixed, and stirred at a speed of 200 r / min for 30 min to obtain a wear-resistant coating.
[0030] Preparation of highly wear-resistant stainless steel belts: The surface of the steel strip body is polished with sandpaper, and then the steel strip body is cleaned with ethanol and dried in the air. After the steel strip body is dried, the spray gun is kept about 20 cm away from the surface of the steel strip body, and vertical reciprocating spraying is performed. It is placed in an environment of 35°C for 48 hours until it is completely cured, so that a wear-resistant coating is formed on the surface of the steel strip body to obtain a highly wear-resistant stainless steel strip.
[0031] Example 2 Preparation of modified nanocellulose: 15 g of nanocellulose was added to 125 g of sodium hydroxide, treated at 80° C. for 3 h, then washed with deionized water until neutral, dried at 60° C., added to 125 g of dimethyl sulfoxide solution after drying, treated at 80° C. for 3 h, and washed with deionized water to obtain prefabricated nanocellulose; 37% by mass of hydrogen chloride, 98% by mass of sulfuric acid and deionized water were mixed in a mass ratio of 1:3:6 to obtain a mixed acid solution, the prefabricated nanocellulose was mixed with the mixed acid solution, and then acid hydrolyzed at 65° C. for 8 h, a large amount of deionized water was added after hydrolysis, and a centrifuge was used to centrifuge at a speed of 10000 r / min to obtain modified nanocellulose.
[0032] Preparation of amino graphene: 10 g of graphene was mixed with 1000 mL of deionized water and ultrasonically treated for 15 min to obtain a graphene dispersion. 20 g of polyvinyl pyrrolidone was added to the graphene dispersion and magnetically stirred for 30 min. The mixture was then heated to 90° C., 4.5 g of polyetheramine was added, and the mixture was stirred at 400 r / min and heated to reflux for 10 h. After the reaction, the mixture was filtered until the pH value of the system was 7, and finally freeze-dried at -20° C. to obtain amino graphene.
[0033] Preparation of modified graphene: 5.13 g of aminated graphene was mixed with 500 g of deionized water, and after ultrasonic treatment for 15 min, ammonia water was added to adjust the pH value of the system to 9. In an atmosphere of nitrogen protection, 14.87 g of styrene and 20 mL of a 15 mg / mL potassium persulfate aqueous solution were added while stirring at a speed of 500 r / min. The stirring condition was maintained, and the temperature was raised to 90° C. for reaction for 6 h. 262.5 g of hydrazine hydrate was added, and the reaction was continued under stirring conditions and a temperature of 90° C. for 1 h. After the reaction, the mixture was freeze-dried at -20° C. to obtain modified graphene.
[0034] Preparation of graphene composite components: After mixing 10.71 g of polyvinyl alcohol with deionized water, the temperature was raised to 95°C, 15 g of modified graphene, 4.29 g of modified nanocellulose and 30 g of sodium chloride were added, and then 120 g of n-hexadecane was added. The mixture was sheared and emulsified at a speed of 6000 r / min for 2 min, and then transferred to an ice water bath and ultrasonically treated at a power of 30% for 3 min to obtain a graphene composite component.
[0035] Preparation of wear-resistant coating: 115 g of waterborne polyurethane, 64 g of epoxy resin, 26 g of graphene composite component, 5 g of dispersant, 9 g of leveling agent and 4 g of defoaming agent were mixed, and stirred at a speed of 200 r / min for 30 min to obtain a wear-resistant coating.
[0036] Preparation of highly wear-resistant stainless steel belts: The surface of the steel strip body is polished with sandpaper, and then the steel strip body is cleaned with ethanol and dried in the air. After the steel strip body is dried, the spray gun is kept about 20 cm away from the surface of the steel strip body, and vertical reciprocating spraying is performed. It is placed in an environment of 35°C for 48 hours until it is completely cured, so that a wear-resistant coating is formed on the surface of the steel strip body to obtain a highly wear-resistant stainless steel strip.
[0037] Example 3 Preparation of modified nanocellulose: 15 g of nanocellulose was added to 125 g of sodium hydroxide, treated at 80° C. for 3 h, then washed with deionized water until neutral, dried at 60° C., added to 125 g of dimethyl sulfoxide solution after drying, treated at 80° C. for 3 h, and washed with deionized water to obtain prefabricated nanocellulose; 37% by mass of hydrogen chloride, 98% by mass of sulfuric acid and deionized water were mixed in a mass ratio of 1:3:6 to obtain a mixed acid solution, the prefabricated nanocellulose was mixed with the mixed acid solution, and then acid hydrolyzed at 65° C. for 8 h, a large amount of deionized water was added after hydrolysis, and a centrifuge was used to centrifuge at a speed of 10000 r / min to obtain modified nanocellulose.
[0038] Preparation of amino graphene: 10 g of graphene was mixed with 1000 mL of deionized water and ultrasonically treated for 15 min to obtain a graphene dispersion. 20 g of polyvinyl pyrrolidone was added to the graphene dispersion and magnetically stirred for 30 min. The mixture was then heated to 90° C., 4.5 g of polyetheramine was added, and the mixture was stirred at 400 r / min and heated to reflux for 10 h. After the reaction, the mixture was filtered until the pH value of the system was 7, and finally freeze-dried at -20° C. to obtain amino graphene.
[0039] Preparation of modified graphene: 5.41 g of aminated graphene was mixed with 500 g of deionized water, and after ultrasonic treatment for 15 min, ammonia water was added to adjust the pH value of the system to 9. In an atmosphere of nitrogen protection, 14.59 g of styrene and 20 mL of a 15 mg / mL potassium persulfate aqueous solution were added while stirring at a speed of 500 r / min. The stirring condition was maintained, and the temperature was raised to 90° C. for reaction for 6 h. 262.5 g of hydrazine hydrate was added, and the reaction was continued under stirring conditions and a temperature of 90° C. for 1 h. After the reaction, the mixture was freeze-dried at -20° C. to obtain modified graphene.
[0040] Preparation of graphene composite components: After mixing 10.87 g of polyvinyl alcohol with deionized water, the temperature was raised to 95°C, 14.78 g of modified graphene, 4.35 g of modified nanocellulose and 30 g of sodium chloride were added, and then 120 g of n-hexadecane was added. The mixture was sheared and emulsified at a speed of 6000 r / min for 2 min, and then transferred to an ice water bath and ultrasonically treated at a power of 30% for 3 min to obtain a graphene composite component.
[0041] Preparation of wear-resistant coating: 110 g of waterborne polyurethane, 58 g of epoxy resin, 23 g of graphene composite component, 4 g of dispersant, 8 g of leveling agent and 3 g of defoaming agent were mixed, and stirred at a speed of 200 r / min for 30 min to obtain a wear-resistant coating.
[0042] Preparation of highly wear-resistant stainless steel belts: The surface of the steel strip body is polished with sandpaper, and then the steel strip body is cleaned with ethanol and dried in the air. After the steel strip body is dried, the spray gun is kept about 20 cm away from the surface of the steel strip body, and vertical reciprocating spraying is performed. It is placed in an environment of 35°C for 48 hours until it is completely cured, so that a wear-resistant coating is formed on the surface of the steel strip body to obtain a highly wear-resistant stainless steel strip.
[0043] Example 4 Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that when preparing modified graphene, the amount of amino graphene used is 6.25g, and the amount of styrene used is 13.75g.
[0044] Example 5 Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that when preparing modified graphene, the amount of amino graphene used is 4.76g, and the amount of styrene used is 15.24g.
[0045] Example 6 Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that when preparing the modified graphene, the amino graphene is replaced by ordinary graphene.
[0046] Example 7 Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that when preparing the graphene composite component, the amount of modified graphene used is 13.85g, the amount of modified nanocellulose used is 4.62g, and the amount of polyvinyl alcohol used is 11.53g.
[0047] Example 8 Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that when preparing the graphene composite component, the amount of modified graphene used is 15.62g, the amount of modified nanocellulose used is 4.11g, and the amount of polyvinyl alcohol used is 10.27g.
[0048] Example 9 Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that when preparing the graphene composite component, the modified graphene is replaced by amino graphene.
[0049] Example 10 Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that when preparing the graphene composite component, the modified nanocellulose is replaced by ordinary nanocellulose.
[0050] Embodiment 11 Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that when preparing the graphene composite component, only the modified graphene, modified nanocellulose and polyvinyl alcohol are physically mixed.
[0051] Example 12 Example 12 is based on Example 3. The difference between Example 12 and Example 3 is that polyvinyl alcohol is not added when preparing the graphene composite component.
[0052] Example 13 Example 13 is based on Example 3. The difference between Example 13 and Example 3 is that modified nanocellulose is not added when preparing the graphene composite component.
[0053] Comparative Example 1 Comparative Example 1 is based on Example 3. In Comparative Example 1, when preparing the graphene composite component, the modified graphene is replaced with ordinary graphene.
[0054] Comparative Example 2 Comparative Example 2 is based on Example 3, and in Comparative Example 2, the graphene composite component is replaced with ordinary graphene.
[0055] Performance testing The following performance tests were performed on the samples of Examples 1-13 and Comparative Examples 1-2: (1) Wear resistance test A Bruker UMT-2 friction and wear machine was used with a load of 70N, a rotation speed of 500r / min, a friction radius of 2mm, and a test time of 30min to test the wear of the samples. Each sample was tested three times, and the test results were filled in Table 1.
[0056] (2) Strength performance test The corrosion resistance of the samples was tested according to GB / T 10125-2012 Artificial Atmosphere Corrosion Test-Salt Spray Test. Each sample was tested three times and the test results were filled in Table 1.
[0057] Table 1 Performance test results of samples of Examples 1-13 and Comparative Examples 1-2 Data analysis Combined with Table 1, it can be seen that the wear amount of Examples 1-3 is 4.5 mg or less, indicating that the stainless steel belt prepared in the present application has good wear resistance; the tensile strength of Examples 1-3 is 592 MPa or more, and the impact toughness is 211 J or more, indicating that the stainless steel belt prepared in the present application has good mechanical strength.
[0058] In Example 4 and Example 5, when preparing modified graphene, the mass ratio between the aminated graphene and styrene is not within the scope defined in the present application. When the amount of styrene used is too little, the loading amount of the aminated graphene is too little, and it is difficult to further overcome the van der Waals force between the graphene sheets, and the dispersibility in the system decreases, and the compatibility of the aminated graphene also decreases; when the amount of styrene used is too much, the styrene coats the aminated graphene too much, which affects the size of the aminated graphene, thereby reducing the size uniformity of the modified graphene, reducing the dispersibility in the system, and affecting the stability of the wear-resistant coating. Therefore, the performance of Example 4 and Example 5 is reduced.
[0059] In Example 6, when preparing modified graphene, the aminated graphene is replaced with ordinary graphene. The compatibility of the non-aminated graphene is reduced. At the same time, the binding ability with styrene is reduced, and the loading amount of styrene is difficult to be further increased. Therefore, the dispersion performance between the graphene sheets is reduced, and the graphene is agglomerated, which affects the stability of the wear-resistant coating. Therefore, the performance of Example 6 is reduced.
[0060] In Examples 7 and 8, when preparing graphene composite components, the mass ratios of modified graphene, modified nanocellulose and polyvinyl alcohol are not within the range specified in the present application. When the content of modified graphene is too much or too little, it will affect the combination with modified cellulose to form a stable three-dimensional network structure. At the same time, the combination performance of polyvinyl alcohol and modified graphene is also reduced, and it is difficult to further improve the overall dispersibility of the system. Therefore, the performance between Examples 7 and 8 is reduced.
[0061] In Example 9, when preparing the graphene composite component, the modified graphene is replaced with aminated graphene. The dispersion performance between the sheets of aminated graphene alone is difficult to be further improved, so the graphene agglomerates in the system, thereby affecting the stability of the wear-resistant coating.
[0062] In Example 10, when preparing the graphene composite component, the modified nanocellulose is replaced with ordinary nanocellulose. The unmodified nanocellulose is difficult to form a stable shell on the surface of the graphene composite component, which reduces the stability of the graphene composite component and affects the performance of the wear-resistant coating.
[0063] The graphene composite component prepared by physically mixing only the modified graphene, modified nanocellulose and polyvinyl alcohol is difficult to form a stable cross-linked network, resulting in a decrease in the stability of the wear-resistant coating, and thus the performance of implementation 11 is reduced.
[0064] The dispersion performance of the components in the graphene composite component without adding polyvinyl alcohol is difficult to be further improved, and agglomeration occurs in the system, thereby affecting the overall stability of the system, so the performance of implementation 12 is reduced.
[0065] When modified nanocellulose is not added, it is difficult to form a stable cross-linked network with the modified graphene, which causes the wear resistance and stability of the wear-resistant coating to decrease. Therefore, the performance of Example 13 decreases.
[0066] In Comparative Example 1, the modified graphene is replaced with ordinary graphene, and the compatibility of the graphene that has not been modified with amino groups is reduced. At the same time, it is difficult to further improve the dispersion effect of the graphene sheets without styrene treatment. The graphene is dispersed only by polyvinyl alcohol, and the dispersion performance is difficult to further improve. The graphene agglomerates in the system, affecting the overall stability of the wear-resistant coating. Therefore, the performance of Comparative Example 1 is reduced.
[0067] In Comparative Example 2, the graphene composite component is replaced with ordinary graphene, and the graphene is severely agglomerated in the system, which affects the overall stability of the wear-resistant coating, so the performance of Comparative Example 2 is reduced.
[0068] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A highly wear-resistant stainless steel belt, characterized in that: It includes a steel strip body and a wear-resistant coating, wherein the wear-resistant coating is formed by attaching the wear-resistant coating to the surface of the steel strip body, and the wear-resistant coating includes the following components in parts by weight: 105-115 parts of polyurethane, 52-64 parts of epoxy resin, 20-26 parts of graphene composite component, 3-5 parts of dispersant, 7-9 parts of leveling agent, 2-4 parts of defoaming agent; The graphene composite component comprises modified graphene, modified nanocellulose and polyvinyl alcohol.
2. A highly wear-resistant stainless steel belt according to claim 1, characterized in that: The modified graphene includes amination graphene and styrene.
3. A highly wear-resistant stainless steel belt according to claim 2, characterized in that: The amino graphene is prepared by the following method: Graphene and water are mixed by ultrasound to obtain a graphene dispersion, polyvinyl pyrrolidone is added to the graphene dispersion, polyether amine is added after magnetic stirring, stirred and heated to reflux for reaction, filtered after the reaction, freeze-dried to obtain amino graphene.
4. A highly wear-resistant stainless steel belt according to claim 2, characterized in that: The modified graphene is prepared by the following method: The aminated graphene is mixed with water, and after ultrasonic treatment, ammonia water is added, styrene and potassium persulfate aqueous solution are added while stirring, the stirring condition is maintained, the temperature is increased for reaction, hydrazine hydrate is added, the reaction is continued, and freeze-drying is performed after the reaction to obtain modified graphene.
5. A highly wear-resistant stainless steel belt according to claim 4, characterized in that: The mass ratio of the amino graphene to styrene is 1:(2.5-2.9).
6. The highly wear-resistant stainless steel belt according to claim 1, characterized in that: The graphene composite component is prepared by the following method: The polyvinyl alcohol and water are mixed and heated, and modified graphene, modified nanocellulose and sodium chloride are added, and then n-hexadecane is added, sheared and emulsified, and then transferred to an ice water bath for ultrasonic treatment to obtain a graphene composite component.
7. A highly wear-resistant stainless steel belt according to claim 6, characterized in that: The modified nanocellulose is prepared by the following method: The nanocellulose is added to sodium hydroxide for treatment, washed and dried, added to dimethyl sulfoxide solution for treatment, and washed to obtain prefabricated nanocellulose; hydrogen chloride, sulfuric acid and water are mixed to obtain a mixed acid solution, the prefabricated nanocellulose is mixed with the mixed acid solution, acid hydrolyzed, a large amount of water is added after hydrolysis, and centrifuged to obtain modified nanocellulose.
8. The highly wear-resistant stainless steel belt according to claim 6, characterized in that: The mass ratio of the modified graphene, modified cellulose and polyvinyl alcohol is (3.3-3.5):1:2.
5.
9. The highly wear-resistant stainless steel belt according to claim 1, characterized in that: The wear-resistant coating is prepared by the following method: The waterborne polyurethane, epoxy resin, graphene composite component, dispersant, leveling agent and defoamer are mixed and stirred to obtain the wear-resistant coating.
10. The highly wear-resistant stainless steel belt according to claim 1, characterized in that: The invention comprises the following preparation method: The surface of the steel strip body is polished, and then the steel strip body is cleaned with ethanol and dried. The wear-resistant coating is sprayed vertically and reciprocatingly on the surface of the steel strip body and solidified, so that a wear-resistant coating is formed on the surface of the steel strip body to obtain a highly wear-resistant stainless steel strip.